Teachers' Readiness in Implementing Deep Learning: Managerial Studies in Islamic Education - Fitri Afrika Sari; Enung Hasanah; Dian Hidayati (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
The Ministry of Primary and Secondary Education of the Republic of Indonesia, through the Center for Curriculum and Learning (Puskurjar), emphasizes the importance of deep learning learning as part of educational transformation to improve the quality of learning. However, until now, the mapping of teacher readiness to implement it and the role of school managerialism, especially in Muhammadiyah schools, which are Islamic-based, remains unknown. This study aims to explore teacher readiness in implementing the deep learning learning approach of managerial studies in Islamic education, examining several key aspects, understanding the role of school management in preparing teachers to implement deep learning learning from knowledge of deep learning learning concepts, skills in designing and implementing lesson plans, attitudes towards policy changes, and the readiness of supporting facilities and infrastructure that are effective and in accordance with Islamic values. The method employed is a qualitative case study approach. Data were collected through interviews with Muhammadiyah school supervisors, principals, teachers, and observations of classroom learning implementation, as well as analysis of teaching module documents to obtain a comprehensive picture of teacher readiness and managerial roles. The collected data will be analyzed using the thematic analysis method, with the help of the atlas.TI application.9 The results of the study show that the principal and foundation's management facilitate teachers in preparing the implementation of deep learning learning such as holding training, workshops and the existence of learning communities so that this can influence teachers' understanding of the concept of knowledge about deep learning learning that emphasizes awareness, meaningful and joyful, the accuracy of teachers in choosing strategies in designing teaching modules with learning methods that integrate Islamic and contextual values ​​such as problem-based learning, as well as facilities and infrastructure that support the learning process that honors students by implementing the principle of honoring and activating students in the classroom.